Knowledge Analysis of Pregnant Mothers About Newborn Treatment - Diah Nurhidayati; Tuti Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims : Most of the newborn care experienced by the community is a lack of knowledge in newborn care, especially umbilical cord care. This study aimed to analysis of knowledge of pregnant women about newborn care at Panggang Island Health Center, North Seribu Islands in 2021.  Design : Analytical with cross sectional.   Methods : The data used primary data from the results of distributing questionnaires. The data collection instrument used a self-developed knowledge questionnaire. The analytical method used univariate analysis and bivariate analysis with Chi-Square test. Results: Most of the respondents have sufficient knowledge, age 20-35 years, secondary education, non-media sources of information and their husbands are not supportive. There is a relationship between age, education, parity, sources of information and husband's support and knowledge of pregnant women about newborn care.  Conclusions : There is a relationship between age, education, parity, sources of information and husband's support and knowledge of pregnant women about newborn care. Further research can be done to increase the knowledge of pregnant mothers about newborn treatment so that newborn care can be optimized.